Malware Developing Guide: Encryption and Decryption - Jutiphat Chatsomsanga; C. Benjangkaprasert (2022 24th International Conference on Advanced Communication Technology (ICACT), 2022)
This research aims to understand malware from malware author’s view. Starting from Ransomware, we attempt to develop ransomware written in python and encrypt all files in Windows platform without doing harm to crucial system files. In this research we use Asus K550J laptop with Windows 10 education (Build 19042) as a victim machine. We ran encryption and decryption program with different privilege and observe the results as well as time takes to encrypt and decrypt files. Results show that encryption process is much slower than decryption process and both encryption and decryption work slower in the bigger file size.
Keywords: Advanced Malware Detection Techniques; Cryptographic Implementations and Security; Information and Cyber Security